Peran intellectual capital terhadap market to book value dan return on assets dengan research and development sebagai pemoderasi - Pandu Alvi Baskoro; H. Suratno; Syahril Djaddang (Journal of Business & Banking, 2019)
This study aims to support the role of Research and Development on Intellectual Capital on market value (MtBV) and corporate financial performance (ROA).  Using the Pulic model - Intellectual Value Coefficient (VAIC), this study examines the relationship between value added (VAIC) of the three main corporate resources (ie Physical Capital, Human Capital and Structural Capital), the company's market value (MtBV) and corporate finance ( ROA), and also Research and Development (R&D).  The data is gathered from 43 selected banking companies listed on the Indonesia Stock Exchange in 2013-2017.  Data analysis uses multiple regression.  The results show that Intellectual Capital (VAIC) does not affect to market value (MtBV), but the compilation of Intellectual Capital (VAIC) developed by Research and Development (R&D) as full moderation can support market value.  Intellectual Capital (VAIC) affects financial performance (ROA), as well as Intellectual Capital (VAIC) supported by Research and Development (R & D) as a quasi-moderation which also strengthening the financial performance (ROA).Keyword : Intellectual Capital (IC), Market to Book Value (MtBV), Financial Performance (ROA), Research and Development (R&D).